Multifactorial Predictors of Chronic Energy Deficiency (CED) in Pregnant Women: A Literature Review - Dian Refsi; Tasnim Tasnim; Ari Nofitasari (Jurnal Ilmu Multidisiplin, 2025)
Chronic Energy Deficiency (CED) in pregnant women is a critical public health issue in Indonesia, associated with severe consequences such as maternal anemia, hemorrhage, low birth weight, stunting, and perinatal mortality. This literature review analyzed 15 scientific articles sourced from Google Scholar, PubMed, and ResearchGate, to identify factors associated The analysis identified that CED is influenced by direct factors (inadequate nutritional intake, infectious diseases) and indirect factors (extreme maternal age, low education and knowledge, economic constraints, high parity, short birth intervals, food taboos, and irregular antenatal care). While dominant factors varied regionally, maternal economic status, education, dietary patterns, and pre-pregnancy nutritional status were consistently identified as key determinants. In conclusion effective prevention requires comprehensive, context-specific, and multisectoral strategies, including enhanced nutrition education, strengthening household food security, increasing antenatal care coverage, and promoting optimal birth spacing. These interventions are crucial to reduce CED prevalence and improve maternal and child health outcomes.